Synthesis and characterisation of nanostructured copper oxide - Dodoo-Arhin, D.; Leoni, M.; Scardi, P. (Ceramic Engineering and Science Proceedings, 2014)
Nanostructured copper oxides has attracted several research interests over the years due to their interesting optical properties and their potential use in several electronic applications such as solar cells and gas sensors. In this work, reverse micelle microemulsion (a bottom-up approach) and high energy milling (Top-down approach) have been employed for the production of defect-free and highly defective copper oxide nanocrystals. The produced defect-free nanocrystals show good crystallinity with the nanometric nature of the primary domains (20 nm - 4 nm) leading to quantum confinement phenomena. Mechanisms for the nanocrystal formation and growth validated by means of several techniques such as X-ray Diffraction (XRD), Scanning Electron Microscopy (SEM) and Transmission Electron Microscopy (TEM), and Fourier Transform Infra-Red spectroscopy (FTIR) have been proposed. The effect of high energy milling on the microstructure evolution of bulk copper oxide powders was investigated using synchrotron radiation XRD line profile analysis, High Resolution TEM and SEM. The reduction in the average size of crystallites and simultaneous narrowing of the size distribution occurs in the initial minutes of milling. A suitable nanocrystalline microstructure was achieved for a milling of ca. 20 min with asymptotic limit of about 10 nm. A high density of dislocations (≈4.2×10-16 m-2) was introduced in the system in the size reduction process.